The Influence of Work-Life Balance on Project Performance of Medical and Paramedical Professionals at RSUD Dr. Gunawan Mangunkusumo with Co-Worker Relationship Quality as a Moderating Role - Nada Ulayya Martaningtyas; M. Farid Wajdi (Universitas KH. Abdul Chalim Mojokerto, 2025)
Work-Life Balance (WLB) has become a crucial component of juggling work and personal obligations, especially for medical professionals who have a lot on their plate. With an emphasis on the moderating function of Co-worker Relationship Quality (CwRQ), this study examines the effect of WLB on project performance among medical and paramedical professionals at RSUD Dr. Gunawan Mangunkusumo. Partial Least Squares (PLS) was used to examine the quantitative data that was gathered from 147 respondents using structured questionnaires. WLB has a beneficial impact on project performance, according to the data (β=0.418, p < 0.001). Additionally, CwRQ enhances the association between WLB and project performance (β=0.382, p < 0.001) in addition to having a direct favorable impact on project performance (β=0.359, p < 0.001). These results highlight how crucial it is to have a healthy work-life balance and cultivate positive connections with coworkers in order to improve project success in healthcare settings.